2014
DOI: 10.1039/c3em00487b
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated public health risks caused by overestimated VOC removal in wastewater treatment processes

Abstract: The uncontrolled release of volatile organic compounds (VOCs) from wastewater treatment plants (WWTPs) and the adverse health effects on the public have been of increasing concern. In this study, a lab-scale bioreactor was prepared to analyze the mass distribution of three aromatic (benzene, toluene, and xylenes) and four chlorinated VOCs (chloroform, carbon tetrachloride, trichloroethylene, and tetrachloroethylene) among the air, water and sludge phases in wastewater treatment processes. The VOC distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…1 km) to the housing estate located uphill 30 m above the level of the settlement tanks, considering the prevalence of western winds in the Greater Poland district [26] and terrain characteristics (slope, natural forest barrier limiting the eastern winds in the area), we suspect a common factor – presumably waterborne and/or volatile waste products. Volatile organic compounds may be dangerous for wastewater treatment plant workers and inhabitants of nearby houses [27, 28]. The highest levels of these compounds are emitted by a primary clarifier, while the concentration of selected chemicals in one reported case exceeded the regulatory threshold limit even within up to 4 km distance from the wastewater treatment plant [28].…”
Section: Discussion Of the Issue Of Pemphigus Triggering In Relation mentioning
confidence: 99%
See 1 more Smart Citation
“…1 km) to the housing estate located uphill 30 m above the level of the settlement tanks, considering the prevalence of western winds in the Greater Poland district [26] and terrain characteristics (slope, natural forest barrier limiting the eastern winds in the area), we suspect a common factor – presumably waterborne and/or volatile waste products. Volatile organic compounds may be dangerous for wastewater treatment plant workers and inhabitants of nearby houses [27, 28]. The highest levels of these compounds are emitted by a primary clarifier, while the concentration of selected chemicals in one reported case exceeded the regulatory threshold limit even within up to 4 km distance from the wastewater treatment plant [28].…”
Section: Discussion Of the Issue Of Pemphigus Triggering In Relation mentioning
confidence: 99%
“…Volatile organic compounds may be dangerous for wastewater treatment plant workers and inhabitants of nearby houses [27, 28]. The highest levels of these compounds are emitted by a primary clarifier, while the concentration of selected chemicals in one reported case exceeded the regulatory threshold limit even within up to 4 km distance from the wastewater treatment plant [28]. …”
Section: Discussion Of the Issue Of Pemphigus Triggering In Relation mentioning
confidence: 99%
“…studied the contribution of oxidative stress caused by occupational health hazards to the impaired lung functions among sewage workers. Statistically significant decreases were observed in several parameters, such as peak expiratory, force expiratory volume in first second, and forced expiratory flow at 25%-75% of volume as percentage of vital capacity, and it was also found that increased levels of serum malondialdehyde in sewage workers were significant Yang, Wang et al (2014). studied the mass distribution of three aromatic (benzene, toluene, and xylenes) and four chlorinated volatile organic compounds (chloroform, carbon tetrachloride, trichloroethylene, and tetrachloroethylene) among the air, water, and sludge phases in wastewater treatment processes with a lab-scale Water Environment Research, Volume 87, Number 10-Copyright © 2015 Water Environment Federation bioreactor and an investigation of a full-scale WWTP in northern China.…”
mentioning
confidence: 92%
“…Chlorinated volatile organic compounds (Cl-VOCs) and aromatic hydrocarbons (BTEXs; benzene, toluene, and xylenes) are ubiquitous contaminants frequently detected in the environment. Therefore, human exposure to Cl-VOCs and BTEX is very common; they enter the body through multiple routes, such as inhalation, ingestion, and dermal absorption [3][4][5]. The toxicity of these compounds is increased by the fact that VOCs are strongly lipophilic with a capacity to concentrate in fat deposits by determining a long-term exposure [6,7].…”
Section: Introductionmentioning
confidence: 99%